Associations Between ADHD Symptoms and Maternal and Birth Outcomes: An Exploratory Analysis in a Multi-Country Cohort of Expectant Mothers. Issue 14 (December 2022) - Murray, Aja Louise; Taut, Diana; Baban, Adriana; Hemady, Chad Lance; Walker, Susan; Osafo, Joseph; Sikander, Siham; Tomlinson, Mark; Toit, Stefani Du; Marlow, Marguerite; Ward, Catherine L.; Fernando, Asvini; et al.
Objective: ADHD symptoms can adversely impact functioning in a range of domains relevant for maternal well-being and fetal development; however, there has been almost no research examining their impact during pregnancy. We aimed to address this gap. Method: We used data ( n = 1, 204) from a longitudinal birth cohort study spanning eight countries to address this gap. Results: ADHD symptoms in the third trimester of pregnancy were associated with lower social support from family ( b = −0.16, p = .031), friends ( b = −0.16, p = .024), and significant others ( b = −0.09, p = .001); higher stress ( b = 0.34, p < .001) and depressive symptoms ( b = 0.31, p < .001), and increased likelihood of an unwanted pregnancy ( b = 0.30, p = .009). Significant associations with tobacco use ( b = 0.36, p = .023) and premature birth ( b = 0.35, p = .007) did not survive correction for multiple comparisons and there were no significant associations with alcohol use, low birth weight, or unplanned pregnancy. Conclusion: Results suggest that women with ADHD symptoms could benefit from earlier, more regular screening for mental health difficulties and greater mental health support during pregnancy.